2022
DOI: 10.3390/molecules27041319
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Quercetin 3-O-Glucuronide against Cisplatin Cytotoxicity in Renal Tubular Cells

Abstract: Quercetin, a flavonoid with promising therapeutic potential, has been shown to protect from cisplatin nephrotoxicity in rats following intraperitoneal injection, but its low bioavailability curtails its prospective clinical utility in oral therapy. We recently developed a micellar formulation (P-quercetin) with enhanced solubility and bioavailability, and identical nephroprotective properties. As a first aim, we herein evaluated the oral treatment with P-quercetin in rats, which displayed no nephroprotection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Quercetin 3 -O-glucuronide has potent antioxidant and anti-inflammatory properties, immune-boosting properties, and potential therapeutic effects in the treatment of diabetes [71]. It may also have unique benefits in improving exercise performance and recovery and protecting the liver against damage caused by toxins [72] ) at m/z 609.1466 in mint leaves. Isorhamnetin has potent anti-cancer and anti-inflammatory properties, cardiovascular benefits, reduced inflammation and oxidative stress, and improved blood pressure and cholesterol levels.…”
Section: Flavonolsmentioning
confidence: 99%
“…Quercetin 3 -O-glucuronide has potent antioxidant and anti-inflammatory properties, immune-boosting properties, and potential therapeutic effects in the treatment of diabetes [71]. It may also have unique benefits in improving exercise performance and recovery and protecting the liver against damage caused by toxins [72] ) at m/z 609.1466 in mint leaves. Isorhamnetin has potent anti-cancer and anti-inflammatory properties, cardiovascular benefits, reduced inflammation and oxidative stress, and improved blood pressure and cholesterol levels.…”
Section: Flavonolsmentioning
confidence: 99%
“…It has been reported that QUE protects granulosa cells from damage caused by oxidative stress in pigs [25], goats [57], buffaloes [28], and chickens [58]. Moreover, QUE alleviates the toxic effects of heavy metals such as copper [59], cadmium [60], cisplatin [61], iron [62], and lead [63]. And a physiological dose of QUE could remove ROS and effectively reverse the decrease in MMP [64][65][66], thus exerting its antioxidant effect to protect cells.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin exerts beneficial effects on type 2 diabetes potentially by inhibiting pancreatic iron deposition and pancreatic β cells ferroptosis [ 94 ]. Quercetin-3-O-glucuronide is a metabolite of quercetin that has been shown to block the role of renal platinum in tubular cells and can prevent tubular toxicity and play a renal protective role [ 95 ].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%